Nature of the multicomponent crystal of salicylic acid and 1, 2-phenylenediamine. Issue 4 (23rd December 2019) - Tier, Aniele Z.; Wust, Keli M.; Vieira, Jean C. B.; Sardo, Mariana; Čendak, Tomaž; Mafra, Luís; Rocha, João; Gindri, Izabelle M.; Hörner, Manfredo; Frizzo, Clarissa P.
Abstract : The synthesis and characterization of the multicomponent crystal formed by salicylic acid and 1, 2-phenylenediamine (a diarylamine) are reported. Abstract : The synthesis and characterization of the multicomponent crystal formed by salicylic acid and 1, 2-phenylenediamine (a diarylamine) are reported. The crystals are in the salt rather than cocrystal form, as witnessed by X-ray photoelectron spectroscopy, solid-state NMR, and infrared spectroscopy. 1 H double-quantum-single-quantum NMR was pivotal in confirming the proton transfer from the salicylic acid to the amine group of the basic coformer 1, 2-phenylenediamine. DFT calculations were used for the geometry optimization of the hydrogen atom positions, and for calculating the NMR chemical shifts of the two possible salt/cocrystal X-ray diffraction models.